2009
DOI: 10.1016/j.marchem.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium studies of copper-dissolved organic matter complexation in water column of the stratified Krka River estuary (Croatia)

Abstract: To cite this version:Yoann Louis, Cédric Garnier, Véronique Lenoble, Stéphane Mounier, Neven Cukrov, et al.. Kinetic and equilibrium studies of copper-dissolved organic matter complexation in water column of the stratified Krka River estuary (Croatia). Marine Chemistry, Elsevier, 2009, 114, pp.An interaction of dissolved natural organic matter (DNOM) with copper ions in the water column of the stratified Krka River estuary (Croatia) was studied. The experimental methodology was based on the differential pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 56 publications
4
91
2
1
Order By: Relevance
“…In line with this, as the particulate fraction is low, the contribution of potentially released metals to the dissolved pool is also probably minor. The subsurface maximum within FSI layer previously reported to occur for organic matter and trace metals (Bilinski et al, 2000;Kniewald et al, 1987;Louis et al, 2009;Zutic and Legovic, 1987) was not registered in our study mainly due to insufficient number of points in the vertical profile (only three points, from which only one in FSI layer). In most cases, the concentrations in FSI layer for all metals were between those measured in two adjacent layers (Table 2).…”
Section: Distribution and Behaviour Of Trace Metals Along The Salinitcontrasting
confidence: 79%
See 4 more Smart Citations
“…In line with this, as the particulate fraction is low, the contribution of potentially released metals to the dissolved pool is also probably minor. The subsurface maximum within FSI layer previously reported to occur for organic matter and trace metals (Bilinski et al, 2000;Kniewald et al, 1987;Louis et al, 2009;Zutic and Legovic, 1987) was not registered in our study mainly due to insufficient number of points in the vertical profile (only three points, from which only one in FSI layer). In most cases, the concentrations in FSI layer for all metals were between those measured in two adjacent layers (Table 2).…”
Section: Distribution and Behaviour Of Trace Metals Along The Salinitcontrasting
confidence: 79%
“…First studies of trace metals , organic matter and SPM (Cauwet, 1991) and biological activities (Denant et al, 1991;Grzetic et al, 1991;Legovic et al, 1991a;Legovic et al, 1991b;Legovic et al, 1991c;Legovic et al, 1994) revealing the low pollution within the estuary were partially confirmed by more recent studies (Bilinski et al, 1992;Bilinski et al, 2000;Cetinic et al, 2006;Louis et al, 2009;Omanović et al, 2006;Supraha et al, 2014). An anthropogenic influence noticed in the estuary was mainly related to the increased nautical tourism in (Louis et al, 2009;Omanović et al, 2006).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations